KAJIAN ANALISIS WACANA HUMOR BAHASA BALI DALAM VIDEO TAKSU NORTH BALI 2 YANG BERJUDUL BATUN DACIN - Wardana, I Putu Surya; Parwati, Pande Made Ratih (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This research aims to analyze the Balinese discourse in the Batun Dacin video produced by Taksu North Bali. The main focus of this study is to identify and examine the elements of Balinese language used in constructing humor, as well as to understand how this discourse reflects social and cultural dynamics within Balinese society. The type of data used in this study is qualitative data in the form of a transcript of conversations in the Batun Dacin video. The primary data source is the Batun Dacin video, which is accessible through social media platforms. This research employs a descriptive discourse analysis method with a critical discourse analysis approach. This approach is chosen to examine the structure and meaning embedded in the humorous discourse, as well as to explore how Balinese language is used to convey social criticism and reinforce cultural norms. The results of the analysis show that in the video, humorous elements such as sarcasm, mockery, misunderstandings, and references to sexuality are used to provide commentary on social phenomena in Balinese society. The humor presented in the video functions not only as entertainment but also as a subtle way to address social issues. Thus, the discourse in Batun Dacin reflects the relationship between language, humor, and the social context.